Formulation of Mocaf Mie with Natural Colors from Purples Sweet Potatoes - Nurjannah, Henny; Lestari, Wanda; Manggabarani, Saskiyanto (Study Program of Nutrition, Public Health Faculty, Institut Kesehatan Helvetia, 2019)
Background: Noodle is one of the popular food products in the community. Purple sweet potato contains large amounts of anthocyanin pigment. Seeing the prospect of great benefits and easily obtained, sweet potatoes can be optimized for use as a source of natural dyes. Objectives: The purpose of this study was to determine the nutrient content of wet noodles and the level of preference for noodles from mocaf flour with natural sweet potato dyes. Material and Method: This type of research is an experiment with a completely randomized design (CRD) with 4 treatments and 2 repetitions to produce 8 experimental designs. Results: The hedonic test results obtained the best formula is F1 with a value of 3.67 categories very like while the hedonic quality test obtained the best formula is F1 with a value of 3.68 categories of purplish, slightly aromatic colour, slightly savoury taste and somewhat chewy texture. The nutritional content of wet noodles are 69.02% water content, 3.67% ash content, 1.03% fat content, 9.77% protein content, 0.34% calcium content and 1.493% phosphorus content. Conclusion: The most preferred wet noodle based on hedonic test and hedonic quality is F1 formula. This wet noodle only has a little nutritional content, further research is needed in order to get the best-wet noodle formulation and has a good nutritional content so that it can be produced as an alternative to wet noodle variations.